Modern tools for managing the climate economy of Kazakhstan - Zhumagulova, A.M.; Yessirkepova, A.M.; Akbayev, E.T.; Baineyeva, P.T. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the article is to examine the effects of climate change and propose appropriate measures to reduce emissions. Methods: The article used systematic, analytical and statistical methods to manage the climate economy. The research methodology draws on qualitative research into current and evolving issues related to the impacts of climate change. To systematize the methods, official statistical data from the Global Change Data Laboratory and the Bureau of National Statistics of the Republic of Kazakhstan were used. Findings: The article analyzes per capita carbon dioxide emissions from fossil fuels and industry, as well as the dynamics of costs and investments in air and climate protection. According to the authors, government policy to ensure reliable energy to achieve sustainable development goals cannot be achieved without taking into account environmental requirements. Reliance on low-cost, carbon-intensive energy solutions while ignoring environmental issues makes it difficult for the country to reduce its carbon emissions. Climate economics must focus on lean production. Conclusions: Modern tools for managing the climate economy should be aimed at effective planning for the use of natural resources, the use of digital technologies to track and manage energy, and investing in enterprises involved in the disposal of food waste.